2004
DOI: 10.1645/ge-3382
|View full text |Cite
|
Sign up to set email alerts
|

Amoebacidal Effects of Serum From the American Alligator (Alligator Mississippiensis)

Abstract: Treatment of axenic Naegleria gruberi cultures with alligator serum resulted in time-dependent amoebacidal activity, with measurable activity at 5 min and maximal activity occurring at 20 min. The amoebacidal activity was concentration dependent, with measurable activity at 25% serum, whereas treatment of amoebas with undiluted serum resulted in only 16% survival. The efficacy was dependent on the concentration of amoebas, with higher survival rates at high amoeba densities and lower survival rates at low amoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 13 publications
6
30
0
2
Order By: Relevance
“…Activity was significantly decreased at temperatures below 15°C, suggesting that alligators may be immunocompromised in the winter when body temperatures are commonly below this threshold. Activity was also significantly decreased at temperatures above 30°C, which supports past research, indicating that physiological processes in the alligator are optimized near this temperature (Merchant et al, 2003;Merchant et al, 2004). In a subsequent study, Merchant and Britton (Merchant and Britton, 2006) found that the lysis of sheep red blood cells by serum from saltwater (Crocodylus porosus) and freshwater (Crocodylus johnstoni) crocodiles required divalent metal ions, was heat sensitive and was unaffected by methylamine; therefore, suggesting that the alternative pathway was responsible for the lysis.…”
Section: Innate Immunitysupporting
confidence: 75%
See 1 more Smart Citation
“…Activity was significantly decreased at temperatures below 15°C, suggesting that alligators may be immunocompromised in the winter when body temperatures are commonly below this threshold. Activity was also significantly decreased at temperatures above 30°C, which supports past research, indicating that physiological processes in the alligator are optimized near this temperature (Merchant et al, 2003;Merchant et al, 2004). In a subsequent study, Merchant and Britton (Merchant and Britton, 2006) found that the lysis of sheep red blood cells by serum from saltwater (Crocodylus porosus) and freshwater (Crocodylus johnstoni) crocodiles required divalent metal ions, was heat sensitive and was unaffected by methylamine; therefore, suggesting that the alternative pathway was responsible for the lysis.…”
Section: Innate Immunitysupporting
confidence: 75%
“…Heating of the alligator serum to 56°C for 30min depleted it of bactericidal activity (complement proteins are heat labile at this temperature), providing direct evidence that the complement system was responsible for the killing. Alligator serum also demonstrated amoebacidal effects against three strains of Naegleria species and four Acanthamoeba species, all of which are reported to be resistant to human complement lysis (Merchant et al, 2004). Antimicrobial and amoebacidal activity occurred at temperatures between 5°C and 40°C, which is the range of internal body temperatures of wild alligators.…”
Section: Innate Immunitymentioning
confidence: 95%
“…Our preliminary findings show that organs lysates of the leafnose viper exhibited antimicrobial activities similar to black cobra, suggesting that it is an important area for further research. Among other reptile species, the serum of American Alligator (Alligator mississippiensis), [28][29][30] plasma of Siamese crocodile (Crocodylus siamensis), 31 and tissue extracts of Nile crocodile (Crocodylus niloticus) 32 have been shown to possess antibacterial as well as antiviral and anti-protist activities. In summary, for the first time we report antimicrobial activity from plasma and internal body organs of the black cobra.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral, morphological and physiological adaptations such as parental care, a four-chambered heart, and osmoregulation capabilities are crocodilian characteristics that distinguish them from other reptilians (Shine, 1988;Mazzotti and Dunson, 1989;Franklin and Axelsson, 1994). The immediate and non-hesitant immune system of crocodilians, in comparison to other vertebrates, is an exceptional evolutionary adaptation in response to wounds from intra-and interspecific conflict in bacteria-laden environments (Merchant et al, 2003(Merchant et al, , 2004(Merchant et al, , 2005. This suite of adaptations may have contributed to their long term persistence in changing environments since the Triassic.…”
Section: Introductionmentioning
confidence: 99%